ANALISIS PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL, FINANCIAL LEVERAGE, DAN UKURAN KAP TERHADAP PERATAAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Pada Perusahaan Go Publik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Luciana Dwiastuti; Restu Agusti; Al Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to test the Effect of Institutional Ownership Structure, Financial Leverage, And Size Of Flattening Kap Profit By Company Size As Variable Moderation.The target population in this study include Property and Real Estate companies listed in Indonesia Stock Exchange in 2011-2014. The samples were selected by purposive sampling method. The data used in this research is secondary data. Data collection method used is the method of documentation. The analytical method used in this research is regression analysis moderation.Based on the data collected and testing has been done on the problem by using the method of regression analysis, it can be concluded: 1) Institutional Ownership has no significant effect on Income smoothing. 2) Financial Leverage has a significant effect on Income smoothing. 3) Auditor Size has a significant effect on Income smoothing. 4) Company Size has no significant effect on Income smoothing. 5) Interaction Institutional Ownership and Firm Size has no significant effect on Income smoothing. 6) Interaction Financial Leverage and Firm Size has a significant effect on Income smoothing. 7) Interaction Firm Size and Firm Size has a significant effect on Income smoothing.Keywords: Institutional Ownership Structure, Financial Leverage, Firm Size, Income Smoothing and Company Size.